An exploration of recreational activities while travelling relative to psychographic tendencies. Issue 3 (1st September 2016) - Merritt, Ryan; Kline, Carol; Crawford, Alleah; Viren, Paige P.; Dilworth, Ginni
ABSTRACT: Through focusing on active and adventure tourism, a niche of travel becoming increasingly relevant today, this study investigated the association between the preferred recreation activities of individuals while travelling and their psychographic profile characteristics based on Plog's [(1972). Why destination areas rise and fall in popularity . Paper presented to the Travel Research Association, Southern California Chapter, Los Angeles] model of allocentricity and psychocentricity. Additionally, we investigated the relevancy of this model using individual's preferred vacation destinations. The activities most likely for respondents to participate in while on vacation were walking, beach activities (sunbathing, walking, and collecting shells), nature walking, swimming, wildlife/nature viewing, and hiking. Results indicated an association between respondent psychographic scores and their projected activity preferences while on vacation.